The Adsorptive Removal of Sulfadiazine Drug from Aqueous Solution Using Poly (Acryl Amide-co-Crotonic Acid) Hydro Gels - Layth Sameer Jasim (Journal of Global Pharma Technology, 2018)
The adsorption of Sulfadiazine drug from aqueous solution has been investigated using acryl amide-co-crotonic acid croos-linked as the adsorbents. Batch kinetics and thermodynamics studies were carried out to evaluate the effect of contact time, ionic strength, pH and temperature. The calculated data were in accordance with Freundlich equation and the adsorption isotherms are of S-curve type according to Giles classification. The results obtained show greater adsorption uptake of the Sulfadiazine than Sulfathiazole on the hydro gels. The adsorption phenomenon was examined as a function of temperature (15, 25, 30 and 35oC). The extents of adsorption of durg on the hydro gels were found to decrease with increasing temperature (exothermic process). The basic thermodynamic functions have also been calculated. Adsorption on hydro gels surfaces was examined as a function of ph. The adsorbed amount of drug on surface was increased as the pH decreased. The adsorption process is affected by the electrolyte concentration. The results indicated an increase adsorption of drug in the presence of sodium hydrochloride.Keywords: Adsorption, Hydro gels, Sulfadiazine, Isotherms, Thermodynamic.